A Modified Buttockectomy as a Limb Salvage Procedure in Ischium Osteosarcoma: A Case Report - KAMAL, ACHMAD FAUZI; DJAJA, YOSHI PRATAMA; KODRAT, EVELINA; SALAMAH, THARIQAH (Indonesian Journal of Cancer, 2015)
Osteosarcoma, which rarely originates from the axial bones such as pelvis, presents a major challenge in limb preservation. We report a 9-year-old girl with osteosarcoma on her buttock. She underwent wide excision âmodified buttockectomyâ to resect the tumour with sciatic nerve involvement. One year after surgery, she was able to walk and no recurrence was found.Â Keywords: buttockectomy, osteosarcomaÂ ABSTRAKOsteosarkoma, tulang aksial seperti pelvis jarang sekali ditemukan, dan menjadi tantangan besar dalam upaya penyelamatan ekstremitas. Kami laporkan satu kasus osteosarkoma pada tulang panggul-daearah bokong pada seorang anak perempuan berusia 9 tahun. Pasien menjalani eksisi luas âbuttockectomyâ yang dimodifikasi untuk mengangkat tumor beserta nervus ischiadikus yang terlibat. Pada pengamatan satu tahun pasca pembedahan, pasien dapat berjalan dan tidak ditemukan tanda-tanda rekurensi.Â Kata Kunci: buttockectomy, osteosarkoma